Investigation of transition symmetry shapes of 160-168Yb nuclei using IBM - Hady, Heiyam Najy; Muttalb, Mohsin Kadhim (Iraqi Journal of Science, 2021)
The interacting boson models, and were used to perform a complete study of even –even 160-168Yb isotopes .The low –lying positive parity states, dynamic symmetries, reduced electric quadrupole transition probability , quadruple momentum , and potential energy surface for 160-168Yb were investigated. Energy level sequences and energy ratios showed the gradual transition of the properties of these nuclei from the γ-unstable features to the rotational features . Adding the pairing parameter to Hamiltonian had a very slight effect on this feature, but it raised the β band, since it represents symmetry breaking such as in γ-unstable features . This applies to the experimental decay scheme of 160-168Yb isotopes. In , proton and neutron quadruple deformation parameters and showed values equal to -1.24 and approximately 0.7, respectively, which supports the same idea in the interacting boson model . A contour plot of the potential energy surface for 160-168Yb isotopes showed that the minimum potential occurs at approximately .